Innovation and practice in management accounting in response to the new healthcare reform in China - LU, CHUN-YI (2018)
This paper explores the innovation and practices in management accounting in response to the new healthcare reform in China over the past 10 years. It tries to figure out how a change in the management accounting systems (MAS) of healthcare institutions was implemented acceptable without much resistance from medical professionals involved. The study conducts the empirical investigations through a mixed qualitative method combining documentary review and semi-structured interview. Employing Broadbent and Laughlin’s Middle Range Theory (MRT) and its skeletal framework, the study focuses on the Shanghai city, which is the typical representative of well-developed cities in China. We divided the whole process into four phases and then discussed it based on a series of official document, as well as the interview data. The findings revealed that the success of internal changes in MAS and decreasing resistance at organizational level is influenced by the involvement of medical professionals in the ongoing changing process. Therefore, it created a new business culture within the health organizations.